Comparison of the Chinese Audience Attitude to Integrated Product Placement and Non-Integrated Product Placement - CUI, YING (2017)
Product placement as an effective marketing strategy has been adopted by many marketing practitioners in recent years. This dissertation aims at comparing audience attitude to different categories of product placement in terms of integrated and non-integrated product placement. It mainly focuses on the context of China. Specifically, it measures the Chinese audience attitude to integrated and non-integrated TV product placement in general and compares the Chinese audience attitude to integrated and non-integrated product placement under the specific conditions of high prominence level and high programme liking degree.